2015
DOI: 10.1109/tnsre.2014.2328296
|View full text |Cite
|
Sign up to set email alerts
|

Online Tremor Suppression Using Electromyography and Low-Level Electrical Stimulation

Abstract: Tremor is one of the most prevalent movement disorders. There is a large proportion of patients (around 25%) in whom current treatments do not attain a significant tremor reduction. This paper proposes a tremor suppression strategy that detects tremor from the electromyographic signals of the muscles from which tremor originates and counteracts it by delivering electrical stimulation to the antagonist muscles in an out of phase manner. The detection was based on the iterative Hilbert transform and stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
134
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(145 citation statements)
references
References 32 publications
4
134
1
6
Order By: Relevance
“…In a recent study (Dosen et al, 2015; Table 1), we observed significant levels of tremor suppression when stimulating muscles below the threshold of direct muscle activation via efferent fibers. This suggests that stimulation of afferent pathways may be an alternative tremor suppression strategy.…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations
“…In a recent study (Dosen et al, 2015; Table 1), we observed significant levels of tremor suppression when stimulating muscles below the threshold of direct muscle activation via efferent fibers. This suggests that stimulation of afferent pathways may be an alternative tremor suppression strategy.…”
Section: Introductionsupporting
confidence: 50%
“…Such treatments, however, can be invasive, expensive, and may not produce effective, long-lasting tremor suppression tremor for all patients. As a potential alternative, studies have suggested the use of external devices to suppress tremor by mechanical loading (Pledgie et al, 2000; Rocon et al, 2007) or electrical stimulation (Javidan et al, 1992; Prochazka et al, 1992; Gillard et al, 1999; Popović Maneski et al, 2011; Gallego et al, 2013; Bó et al, 2014; Dosen et al, 2015). Although the efficacy of both methodologies has been proven, electrical stimulation arguably allows for a more compact and comfortable implementation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aquí cabe destacar el desarrollo de soluciones neuroprotésicas para la supresión de temblores patológicos en el marco de los proyectos europeos TREMOR y NEUROTREMOR, con aproximaciones ligeramente diferentes, en el primer caso mediante estimulación periférica motora (Gallego et al, 2013, Koutsou et al, 2016 y en el segundo caso mediante estimulación periférica sensorial (Dosen et al, 2014;Piazza et al, 2016).…”
Section: Robótica De Rehabilitación Y Asistenciaunclassified